2019
DOI: 10.1111/pan.13577
|View full text |Cite
|
Sign up to set email alerts
|

Single injection ultrasound‐guided rectus sheath blocks for children: Distribution of injected anesthetic

Abstract: Summary Background Single injection ultrasound‐guided rectus sheath blocks are used for postoperative analgesia after midline abdominal incisions, but the ultrasonographic spread of medication posterior to the rectus muscle has not been investigated. Aims The primary goal of this study was to determine the ultrasound‐measured medication spread superiorly and inferiorly after single injection ultrasound‐guided rectus sheath blocks and to calculate the incidence of cases with spread up to the subcostal margin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The authors reported that the LA reached the subcostal line on the right side in 52.9% of patients and on the left side in 36.8% of patients. Hence, they emphasized that it might be more suitable to change the injection point according to the surgical incision site [ 1 ]. Our study has strengths in certain points.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors reported that the LA reached the subcostal line on the right side in 52.9% of patients and on the left side in 36.8% of patients. Hence, they emphasized that it might be more suitable to change the injection point according to the surgical incision site [ 1 ]. Our study has strengths in certain points.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has strengths in certain points. The age group of the children in the study by Visoui et al [ 1 ] constituted a heterogeneous group considering the anthropometric differences among children in the 0-18-year range. In our study, the age group was 0-8 years, which could be expected to be a homogeneous group; moreover, the spread distances were also compared between subgroups of ages comprising children aged 0-2 years and 2-8 years to ensure homogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The layer between the rectus abdominis muscle and the posterior layer of the rectus sheath is the target for the RSB. 7,8 Real-Time, Ultrasound-Guided TTP Block Procedure All block procedures are performed in a sterile fashion as follows: the puncture sites are disinfected, the anesthesiologist performing the puncture wears sterile gloves, and the ultrasound probe is covered with a sterile probe cover (Fig 2, A and Fig 3, A).…”
Section: Presurgical Scan Proceduresmentioning
confidence: 99%